Restitution Slope Affects the Outcome of Dominant Frequency Ablation in Persistent Atrial Fibrillation: CUVIA-AF2 Post-Hoc Analysis Based on Computational Modeling Study - Park, Je-Wook; Lim, Byounghyun; Hwang, Inseok; Kwon, Oh-Seok; Yu, Hee Tae; Kim, Tae-Hoon; Uhm, Jae-Sun; Joung, Boyoung; Lee, Moon-Hyoung; Pak, Hui-Nam (Frontiers in Cardiovascular Medicine, 2022)
Introduction: Although the dominant frequency (DF) localizes the reentrant drivers and the maximal slope of the action potential duration (APD) restitution curve (Smax) reflects the tendency of the wave-break, their interaction has never been studied. We hypothesized that DF ablation has different effects on atrial fibrillation (AF) depending on Smax. Methods: We studied the DF and Smax in 25 realistic human persistent AF model sample (68% male, 60±10 years old). Virtual AF was induced by ramp pacing measuring Smax, followed by spatiotemporal DF evaluation for 34 sec. We assessed the DF ablation effect depending on Smax in both computational modeling and a previous clinical trial, CUVIA-AF (170 persistent AF patients, 70.6% male, 60±11 years old). Results: Mean DF had an inverse relationship with Smax regardless of AF acquisition timing (p<0.001). Virtual DF ablations increased the defragmentation rate compared to pulmonary vein isolation (PVI) alone (p=0.015), especially at Smax<1 (61.5% vs. 7.7%, p=0.011). In post-DF ablation defragmentation episodes, DF was significantly higher (p=0.002), and Smax was lower (p=0.003) than in episodes without defragmentation. In the post-hoc analysis of CUVIA-AF2, we replicated the inverse relationship between Smax and DF (r =-0.47, p<0.001), and we observed better rhythm outcomes of clinical DF ablations in addition to a PVI than of empirical PVI at Smax<1 (harard ratio 0.45, 95% confidence interval [0.22-0.89], p=0.022; log-rank p=0.021) but not at ≥1 (log-rank p=0.177). Conclusions: We found an inverse relationship between DF and Smax and the outcome of DF ablation after PVI was superior at the condition with Smax<1 in both in-silico and clinical trials.